Someone to trust - Balogh, Mary (New York : Jove, 2018)
Widow Elizabeth Overfield and Colin Handrich know there can never be a relationship between them, but an agreement to share a waltz at each ball they attend leaves them questioning what they are willing to sacrifice for love.
Includes excerpt from the author's book: Someone to love (pages [357]-369).
Keywords: Widows -- Fiction; Man-woman relationships -- Fiction; Nobility -- Fiction; Social classes -- Fiction; Historical fiction; Romance fiction